2012
DOI: 10.1063/1.3693400
|View full text |Cite
|
Sign up to set email alerts
|

Spin glass-like phase below ∼210 K in magnetoelectric gallium ferrite

Abstract: Coexistence of spin glass behavior and long-range ferrimagnetic ordering in La-and Dy-doped Co ferrite

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 31 publications
7
23
0
Order By: Relevance
“…This strong f dependence indicates magnetic freezing behavior. The analysis can be made by the Vogel–Fulcher law that characterizes the time scale to overcome the energy barrier in the activation process for magnetically interacting particles, 1/τ=1/τ0exptrue[Ea/kBtrue(TfT0true)true], where E a is the activation energy and T 0 is the characteristic T associated with the inter‐cluster interaction energy . The fitted values from the plot in the inset of Figure b were attained as T 0 = 28.8 K and Ea/kB = 87.8 K. The relatively large activation energy compared to the freezing T , Ea/kB = 2.8 T g , lies in the ordinary range for magnetic cluster‐glass materials …”
mentioning
confidence: 99%
“…This strong f dependence indicates magnetic freezing behavior. The analysis can be made by the Vogel–Fulcher law that characterizes the time scale to overcome the energy barrier in the activation process for magnetically interacting particles, 1/τ=1/τ0exptrue[Ea/kBtrue(TfT0true)true], where E a is the activation energy and T 0 is the characteristic T associated with the inter‐cluster interaction energy . The fitted values from the plot in the inset of Figure b were attained as T 0 = 28.8 K and Ea/kB = 87.8 K. The relatively large activation energy compared to the freezing T , Ea/kB = 2.8 T g , lies in the ordinary range for magnetic cluster‐glass materials …”
mentioning
confidence: 99%
“…15 Though, the magnetic characteristics of GFO are widely studied, 10,13,[16][17][18] intriguingly there is no evidence of its ferroelectric nature. While an early report 19 attributed asymmetrically placed Ga1 ions within the unit cell responsible for observed piezoelectric response of GFO, recent first-principles calculations 20 showed that within the inherently distorted structure of GFO, large ionic displacements with respect to the centrosymmetric positions result in a large spontaneous polarization in the ground state 20 and even hint towards possible ferroelectric switching.…”
mentioning
confidence: 99%
“…3(b). Here, we find that interestingly, the intrinsic bulk capacitance C B exhibits a peak at ∼ 300 K, close to the ferri-paramagnetic transition temperature (T C ) of GFO 17,26 which is indicative of magnetoelectric coupling in GFO.…”
Section: B Complex Electrical Modulus Analysismentioning
confidence: 86%
“…Consequently, such hopping of electrons may cause reorientation of the defect dipoles resulting in the observed Debye like relaxation. 22,24 Another notable feature of bulk relaxation is an abrupt change in the activation energy from 0.087±0.003 eV to 0.027±0.001 eV across 220 K, close to the observed spin-glass transition temperature (∼210 K) 26 in GFO. Although it is tempting to associate this change in activation energy across the spin-glass transition temperature (T s ) to possible correlation between spin waves (magnons) and dipole alignment, much lower magnon excitation energy (∼ 10 -3 eV) are found, in general, in magnetic oxides.…”
Section: B Complex Electrical Modulus Analysismentioning
confidence: 99%